Prediction of Fluid Responsiveness by the Effect of the Lung Recruitment Maneuver on the Perfusion Index in Mechanically Ventilated Patients During Surgery - Morakul, Sunthiti; Prachanpanich, Naruemol; Permsakmesub, Pattarada; Pinsem, Pimwatana; Mongkolpun, Wasineenart; Trongtrakul, Konlawij (Frontiers in Medicine, 2022)
Introduction: Excessive or inadequate fluid administration during perioperative period affects outcomes. Adjustment of volume expansion (VE) by performing fluid responsiveness (FR) test plays an important role in optimizing fluid infusion. Since changes in stroke volume (SV) during lung recruitment maneuver (LRM) can predict FR, and peripheral perfusion index (PI) is related to SV; therefore, we hypothesized that the changes in PI during LRM (∆PILRM) could predict FR during perioperative period. Methods: Patients who were scheduled for elective non-laparoscopic surgery under general anesthesia with a mechanical ventilator and who required VE (250 mL of crystalloid solution infusion over 10 min) were included. Before VE, LRM was performed by a continuous positive airway pressure of 30 cm H2O for 30 sec; hemodynamic variables with their changes (PI, obtained by pulse oximetry; and ∆PILRM, calculated by using ([PI before LRM - PI after LRM]/PI before LRM)*100, were obtained before and after LRM. After SV (measured by esophageal doppler) and PI had returned to the baseline values, VE was infused, and the values of these variables were recorded again, before and after VE. Fluid responders (Fluid-Res) were defined by an increase in SV ≥10% after VE. Receiver operating characteristic curves of the baseline values and ∆PILRM were constructed and reported as areas under the curve (AUC) with 95% confidence intervals, to predict FR. Results: Of 32 mechanically ventilated adult patients included, 13 (41%) were in the Fluid-Res group. Before VE and LRM, there were no differences in the mean arterial pressure (MAP), heart rate, SV, and PI between patients in the Fluid-Res and fluid non-responders (Fluid-NonRes) groups. After LRM, SV, MAP, and, PI decreased in both groups, ∆PILRM was greater in the Fluid-Res group than in Fluid-NonRes group (55.2%±17.8% vs. 35.3%±17.3%, p<0.001, respectively). After VE, only SV and cardiac index increased in the Fluid-Res group. ∆PILRM had the highest AUC (0.81 [ 0.66 - 0.97]) to predict FR with a cut-off value of 40% (sensitivity 92.3%, specificity 73.7%). Conclusions: ∆PILRM can be applied to predict FR in mechanical ventilated patients during the perioperative period.